Assessment of strategic management practices on the performance of firms: a case study of Techiman small taxpayers office of Ghana revenue authority. - Korsah, Esther Agyeiwaa (KNUST, 2025)
A Dissertation Submitted In Partial Fulfilment Of The Requirement For The Award Of A Degree In Master Of Public Administration.